Rancang Bangun Aplikasi Penjadwalan dan Perhitungan Biaya Pembesaran Ikan Lele Sistem Boster pada Farm Fish Boster Centre - Arifin, Bachtiar; Wibowo, Januar; Lemantara, Julianto (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2017)
Farm Fish booster Centre (FFBC) is the implementation of Corporate Social Responsibility (CSR) of PT. Indosco Dwi Jaya Sakti engaged in the research, training and breeding of catfish. Farm Fish booster Centre experienced problems in scheduling and cost calculation enlargement of catfish are used as a guide for the participants. This makes the trainee is still confusion in applying the booster system in the enlargement of catfish that was not uncommon to many participants who experienced failure and loss. Based on the above problems, the necessary application scheduling and cost calculation enlargement of catfish that can output information such as schedules and costs enlargement of catfish are in accordance with the needs of trainees. From the results of application testing scheduling and cost calculation enlargement catfish conclusion that the application made to help trainees in the scheduling process and calculation process catfish enlargement costs in accordance with the needs of trainees.